2002
DOI: 10.1093/hmg/11.24.3039
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of variation within the APOC3/A4/A5 gene cluster in determining plasma triglycerides

Abstract: Since triglycerides (TG) are a major independent risk factor for coronary heart disease, understanding their genetic and environmental determinants is of major importance. Mouse models indicate an inverse relationship between levels of the newly identified apolipoprotein AV (APOAV) and TG concentrations. We have examined the relative influence of human APOA5 variants on plasma lipids, compared to the impact of variation in APOC3 and APOA4 which lie in the same cluster. Single nucleotide polymorphisms (SNPs) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

44
273
11
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(334 citation statements)
references
References 31 publications
44
273
11
6
Order By: Relevance
“…An increase in triglyceride concentrations has been observed in heterozygote subjects for the mutated allele [1,2]. However, another study found no significant increase in triglycerides in heterozygote subjects, but found one among homozygotes for the mutated allele [3]. In our group, we found no significant differences in triglyceride concentrations.…”
contrasting
confidence: 64%
See 1 more Smart Citation
“…An increase in triglyceride concentrations has been observed in heterozygote subjects for the mutated allele [1,2]. However, another study found no significant increase in triglycerides in heterozygote subjects, but found one among homozygotes for the mutated allele [3]. In our group, we found no significant differences in triglyceride concentrations.…”
contrasting
confidence: 64%
“…Its frequency is 12% in Afro-Americans, 16% in Hispanics, 6 to 16% in Caucasians and 7% in a Spanish control cohort [1,2,3,4]. The heterozygote subjects for rare SNP3 allele (C/T) are related to an increase in triglycerides in Hispanic and Caucasian men, although these data were not observed in another study where the increase in triglycerides was only statistically significant in homozygotes for the mutated allele [3]. Hypertriglyceridaemia is the main factor in determining the size of the LDL.…”
Section: Snp3 Polymorphism In Apo A-v Gene Is Associated With Small Dmentioning
confidence: 99%
“…The variants selected were the apolipoprotein A-V (APOA5) single nucleotide polymorphisms (SNPs) rs662799 and rs3135506; the lipoprotein lipase (LPL) SNP rs328; and the glucokinase (GCK) SNP rs1799884, which have been shown in multiple cross-sectional studies to be associated with triacylglycerol (APOA5 and LPL) [16][17][18][19][20][21], HDL-C (LPL) [20,21] and fasting glucose (GCK) [9,22] levels, traits important in the risk of diabetes and cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Human studies have focused upon the association between genetic variation in the APOA5 gene and plasma triglyceride levels. Two common APOA5 polymorphisms, the −1131T→C polymorphism and the c56C→G (S19W) polymorphism in the APOA5 signal peptide, are of particular interest [12,13]. The rare alleles of each polymorphism both show a positive association with elevated plasma triglyceride levels in clinical studies as well as in the general population.…”
Section: Introductionmentioning
confidence: 99%